LINGUISTIC REPRESENTATION OF MOOD IN THE ENGLISH TRANSLATIONS OF "BABURNAMA" BY DIFFERENT TRANSLATORS (American Journal of Technology and Applied Sciences, 2025)
This article provides information about the study of the famous work "Baburnama" by various translators and the fact that the English translators tried to preserve the originality and artistic character of the work, as well as the scientific tendency in the translations in terms of artistic style, the translations of the proverbs in it It is reported that they tried to translate the proverbs in English through an equivalent that is close to their meaning.